A retrospective study on the characteristics of renal pathological grades in HSPN children with mild to moderate proteinuria - Cao, Yan; Shen, Tian; Li, Yongzhen; Shuai, Lanjun; Chen, Qiaoping; Mo, Shuanghong; Li, Canlin; Li, Xiaoyan; Wang, Ying; Wu, Xiaochuan (Frontiers in Pediatrics, 2022)
Objective: To investigate the characteristics of renal pathological grades in Henoch–Schönlein purpura nephritis (HSPN) children with mild to moderate proteinuria and the correlation between pathological grade and severity of proteinuria among this population. Methods: HSPN children who were presented with mild (150 mg < 24h urinary protein < 25 mg/kg) to moderate (25 mg/kg ≤ 24 h urinary protein < 50 mg/kg) proteinuria and performed renal biopsy without steroid ± immunosuppressant treatment in the Second Xiangya Hospital between January 2010 and March 2021 were involved. We retrospectively analyzed the correlation between age, disease course, degree of proteinuria, type of immunoglobulin deposits, C3 deposits in glomeruli and renal pathological grade. Results: (1) 72 HSPN children including 46 boys and 26 girls were included, with a mean age of onset of 9.01±2.65 years old. The majority of these patients (62.5%) had a disease course between 1 week to 1 month. 51 patients presented with mild proteinuria and 21 patients with moderate proteinuria. (2) Renal biopsy results showed that ISKDC Grade IIIa were both predominant in mild proteinuria group (25, 49%) and moderate proteinuria group (11, 52.4%). 32 patients had grade II (44.4%), 2 had grade IIIb (2.8%), 1 had grade IV (1.4%), and 1 had grade VI (1.4%). There was no correlation between age, disease course and renal pathological grade (p > 0.05). (3) In patients with mild proteinuria (n=51), 27 (52.9%) HSPN children had a pathological grade ≥ grade III. In patients with moderate proteinuria (n=21), 13 (61.9%) HSPN children had grade ≥III. There was no significant difference in the proportion of renal pathological grade between the 2 groups (p > 0.05). (4) There was no significant correlation between glomerular C3 deposits or immunoglobulin deposit types and renal pathological grade (p = 0.776 and p = 0.056 respectively). Conclusion: In HSPN children with mild to moderate proteinuria, longer disease course or heavier urinary protein level is not completely parallel with higher renal pathological grade. ISKDC grade IIIa is the most common pathological grade. Clinicians should pay great attention to the renal injury in patients with mild to moderate proteinuria.